Fim da filosofia: uma imagem da filosofia contemporânea - Paiva, Márcio Antônio de (Horizonte, 2004)
This article analyses the issue of ‘the end of philosophy’ in contemporary thought. Setting the framework for the confrontation of philosophy with itself, with science and with some present-time thinkers who dare to predict its end, it attempts to re-establish, through ethical reflection, philosophy as an authentic human knowledge.